1981
DOI: 10.1111/j.1365-2621.1981.tb04171.x
|View full text |Cite
|
Sign up to set email alerts
|

Chia Seed as a Source of Oil, Polysaccharide, and Protein

Abstract: Chia seed, Salvia polystachya, was analyzed as a source of oil, polysaccharide, and protein for possible use by the food industry. Seeds were found to contain 30% oil of which more than 90% was composed of triglycerides. The fatty acid composition of the oil was found to consist mostly of C16:0, ClS:O, C18:2 and C18:3. The protein content of chia seed was found to be 23.4%. A very viscous polysaccharide was isolated from the seeds. Acid hydrolysis followed by gas liquid chromatographic analysis demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
60
1
3

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 11 publications
13
60
1
3
Order By: Relevance
“…82-7.74, 4.07-4.58, 30.22-30-97, 25.32-20.01 and 37.50, and 31.51%, respectively. In general, the values obtained for the proximate composition of the chia nutlets were in agreement with the composition reported in the literature, as follows: 9-23 g protein/100 g (Coates & Ayerza, 1996), 25-35 g lipids/ 100 g (Álvarez-Chávez et al, 2008;Ixtaina et al, 2011), and 18-41 g fiber/100 g (Ayerza & Coates, 2000;Bushway et al, 1981;ReyesCaudillo et al, 2008). Although chia is not commercially grown as a protein source, the protein content is higher than that of traditional crops such as wheat, corn, rice, and oats.…”
Section: Chemical Characterization Of Chia Nutletssupporting
confidence: 78%
See 1 more Smart Citation
“…82-7.74, 4.07-4.58, 30.22-30-97, 25.32-20.01 and 37.50, and 31.51%, respectively. In general, the values obtained for the proximate composition of the chia nutlets were in agreement with the composition reported in the literature, as follows: 9-23 g protein/100 g (Coates & Ayerza, 1996), 25-35 g lipids/ 100 g (Álvarez-Chávez et al, 2008;Ixtaina et al, 2011), and 18-41 g fiber/100 g (Ayerza & Coates, 2000;Bushway et al, 1981;ReyesCaudillo et al, 2008). Although chia is not commercially grown as a protein source, the protein content is higher than that of traditional crops such as wheat, corn, rice, and oats.…”
Section: Chemical Characterization Of Chia Nutletssupporting
confidence: 78%
“…On the other hand, its fiber content is equivalent to 100% of the daily requirements for this nutrient for the adult population. According to Bushway et al (1981) and Reyes-Caudillo et al (2008) the defatted flour has 40% fiber, 5% of which is soluble and it is part of the mucilage. Mucilage contained in chia may hinder the complete enzyme digestion.…”
Section: Chemical Characterization Of Chia Nutletsmentioning
confidence: 99%
“…The iron content of chia is also quite high compared to most other seeds: it has six times more iron than spinach, 1.8 times more than lentils, and 2.4 times more than liver. Bushway et al, (1981); Beltrán-Orozco and Romero, (2003). As illustrated in Table (2) ,it could be observed that the three yoghurt mousses which fortified with chia seeds are richer in minerals with an increase by the ratio increase compared with the control yoghurt mousse.…”
Section: The Minerals Content Of Yoghurt Moussementioning
confidence: 99%
“…(Lamiaceae) is a small shrub native from México where its seeds, known as "chía", are used as food and beverage ingredients. 2,3) In Mexican traditional medicine, this plant is mainly used as purgative and antigastralgic, although other uses such as antipyretic, antipaludic, antihemorragic and emollient, have also been described.2) In an earlier work, we isolated eight clerodane type diterpenes (salvifaricin, linearolactone, dehydrokerlin and polystachynes A-E) from this plant.4) Now, we described the isolation of a further clerodane derivative from this species. …”
mentioning
confidence: 99%
“…(Lamiaceae) is a small shrub native from México where its seeds, known as "chía", are used as food and beverage ingredients. 2,3) In Mexican traditional medicine, this plant is mainly used as purgative and antigastralgic, although other uses such as antipyretic, antipaludic, antihemorragic and emollient, have also been described.…”
mentioning
confidence: 99%